Pengawasan Sistem Distribusi Material Dalam Pembangunan Dinding Penahan Tanah - Mulyati, Ely; Wulandari, Tanti (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2025)
The material distribution process is one of the key aspects in the success of construction projects, especially in the construction of structures such as retaining walls that require timely delivery and maintained material quality. This study aims to analyze and evaluate the material distribution monitoring system in the construction of retaining walls in the environment. The methods used include field observation, interviews with the project implementation team, and collection of logistics data and material distribution schedules. The results of the study indicate that the main challenges in the distribution system are delays in material supply due to disruption of road access and lack of coordination between project divisions. The implementation of a monitoring system based on mapping schedules and distribution points can improve the efficiency of material flow and minimize work delays. Recommendations from this study include improving monitoring through a real-time monitoring system and integrating measurement data to support more precise and adaptive distribution planning based on field conditions. The practical implications of this study are that a structured and data-based material distribution monitoring system is very relevant to be applied to infrastructure projects in areas with limited access, such as hilly areas, remote villages, or disaster-prone areas. With this system, project implementers can anticipate distribution obstacles more accurately, reduce the risk of delays, and maintain the quality and continuity of development as a whole.